Study of Ansa Subclavia: Anatomy, Functions and Repercussions - Rajani Singh; Kavita Gupta (New Horizons in Medicine and Medical Research Vol. 11, 2022)
Ansa subclavia is a nerve fiber joining middle and inferior cervical ganglion. The cord from middle cervical ganglion curves inferiorly the first part of subclavian artery medial to vertebral artery and joins the inferior cervical ganglion. The Ansa subclavia is developmentally preserved and carried forward from rats, guinea pigs, the porcine species and dogs to human beings. Commonly, Ansa subclavia is electrically stimulated in animal models to modulate stimulatory cardiac sympathetic input in Physiologically studies. In elaborative English language literature search only two studies found describing the anatomy of the Ansa subclavia. The aim of this chapter, is to consolidate information related to the gross/applied anatomy and functions of the ansa subclavia and to bring out associated significance.